English Vocabulary Apps for Classroom Use? Results of an Empirical Survey - Danijela Ikonic; Thomas Hawes (Journal of Linguistics and Language Teaching)
Mobile apps (applications) are currently taking over as our most frequently used tools in many situations. As teachers we need to consider whether they ought to be employed in the language classroom, allowed in tests, or referred to for homework. This paper focuses on an experiment in a German vocational school to answer these questions by gauging, firstly, students’ performance in a vocabulary test, with and without access to an app named Quizlet and, secondly, their attitudes to the use of apps for English vocabulary learning via two questionnaires. Responses to the latter showed that every single pupil in the survey uses a mobile phone daily and that a clear majority in every class except one think it would make sense to use their mobile phones to help them with school subjects, primarily because these may be enjoyably employed anywhere, anytime. They feel that apps on their mobile phones motivate better than traditional paper-based classroom materials, especially when there is a game-like element. As for the test, the general improvement in results obtained with the app suggests that it could at the very least be used more extensively in schools. In the test, curiously, the youngest pupils failed to improve their results with Quizlet, but almost every other student category did benefit considerably and there is reason to believe that it would be worth exploiting such apps for vocabulary learning, testing and perhaps for other school subjects in the future.